2014
DOI: 10.2176/nmccrj.2013-0351
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysm at the Proximal Segment of the Anterior Cerebral Artery Associated with Infraoptic Course Anterior Cerebral Artery

Abstract: A 48-year-old man presented a subarachnoid hemorrhage caused by a rupture of a dissecting aneurysm at the proximal segment (A1 segment) of the right anterior cerebral artery (ACA). He also had an anomalous artery named infraoptic course ACA and an agenesis of the contralateral ACA A1 segment. Balloon occlusion test at the bifurcation of the right internal carotid artery demonstrated that the distal segments of the bilateral ACAs were perfused through the infraoptic course ACA. Therefore, we surgically trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As for the descriptions of the origin of the left and right ACAs from one ICA, as described by Burbank and Morris [5], and Kawaji et al [23], a persistent POℓA probably assumed the role of the "second" ACA [32,33,52]. Similar descriptions were also found in the articles of Pokhrel and Bhatnagar [40], and Saikia et al [43], but their schema and/or images do not correspond to the text, i.e.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…As for the descriptions of the origin of the left and right ACAs from one ICA, as described by Burbank and Morris [5], and Kawaji et al [23], a persistent POℓA probably assumed the role of the "second" ACA [32,33,52]. Similar descriptions were also found in the articles of Pokhrel and Bhatnagar [40], and Saikia et al [43], but their schema and/or images do not correspond to the text, i.e.…”
Section: Discussionmentioning
confidence: 72%
“…We think that previously cited frequencies of unilateral ACA aplasia should not be taken as xed values, especially because some authors do not distinguish ACA hypoplasia from aplasia [6,8,17,31,43,54], or aplasia from agenesis [8,16,17,23,42]. Wanibuchi et al [54] described A1 hypoplasia in the text, while they marked the same case as "aplasia" in the table.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different authors reported cases of aneurysms associated with infraoptic ACAs [ 20 ]. These were found on the AComA or on the A1 or A2 segments of the ACA [ 4 , 5 , 7 , 8 , 13 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. An aneurysm on an infraoptic A1 segment of an azygos ACA was also reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%